2017
DOI: 10.1016/s1473-3099(17)30059-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of laminar airflow ventilation on surgical site infections: a systematic review and meta-analysis

Abstract: Background: The role of the operating room's (OR) ventilation system in the prevention of surgical site infection (SSI) is widely discussed and the existing guidelines do not reflect the current evidence. In this context, laminar airflow (LAF) ventilation was compared with conventional ventilation to assess their effectiveness in reducing the risk of SSI.Methods: Medline, EMBASE, Cochrane Central Register of Controlled Trials and WHO regional medical databases were searched from 1990 to 31 January 2014. The se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(102 citation statements)
references
References 56 publications
2
90
1
5
Order By: Relevance
“…A recent meta-analysis concluded that LAF may not be efficient in reducing the risk of SSIs in total hip and knee arthroplasties, and abdominal surgery. 25 After adjustment, our results showed a significant and independent increase air microbial contamination in OR with conventional airflow system in comparison to LAF. Moreover, the airborne particle concentration was consistently lower at incision in ORs with LAF vs conventional airflow and decreased faster during the procedures (Appendix Figure A2).…”
Section: Discussionmentioning
confidence: 67%
“…A recent meta-analysis concluded that LAF may not be efficient in reducing the risk of SSIs in total hip and knee arthroplasties, and abdominal surgery. 25 After adjustment, our results showed a significant and independent increase air microbial contamination in OR with conventional airflow system in comparison to LAF. Moreover, the airborne particle concentration was consistently lower at incision in ORs with LAF vs conventional airflow and decreased faster during the procedures (Appendix Figure A2).…”
Section: Discussionmentioning
confidence: 67%
“…The use of surgical helmet systems, even with tape around the surgical gown cuffs, was not found to reduce the rate of wound contamination during surgery 27 . Similarly, laminar airflow ventilation demonstrated no associated reduction in SSI risk compared with modern operating room ventilation (positive pressure and high-volume and HEPA [high-efficiency particulate air] filtration that can lead to turbulent flow) 28 . In a different high-quality study, a reduction in airborne microorganisms using a device that delivers filtered airflow over the surgical wound reduced the rate of implant infections 29 .…”
Section: Parenteral Antimicrobial Prophylaxismentioning
confidence: 98%
“…In neueren retrospektiven kontrollierten Studien konnte kein protektiver Einfluss von LAF bzw. TAV im Vergleich zu turbulenter Mischlüftung (TML) gezeigt werden [157,[364][365][366][367][368]. Alle einschlägigen aktuellen Studien sind durch Limitationen gekennzeichnet: Zum Teil ist unbekannt, in welchem Ausmaß sich sterile Flächen außerhalb des TAV-Schutzbereichs befanden; orthopädische Spätinfek-tionen sind nicht erfasst [369,370].…”
Section: Bauliche Bedingungenunclassified